Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 20



Work Step by Step

Using the distributive property, the given expression simplifies to: $\frac{3a-b-4a+3b}{a-6b-4b-3a}$ =$\frac{3a-4a-b+3b}{a-3a-6b-4b}$ =$\frac{a(3-4)-b(1-3)}{a(1-3)-b(6+4)}$ =$\frac{a(-1)-b(-2)}{a(-2)-b(10)}$ =$\frac{-a+2b}{-2a-10b}$ We then substitute $a=-1$ and $b=3$ in the expression and simplify: $\frac{-a+2b}{-2a-10b}$ =$\frac{-(-1)+2(3)}{-2(-1)-10(3)}$ =$\frac{1+6}{2-30}$ =$\frac{7}{-28}$ =$-\frac{1}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.